PELAKSANAAN CSR PT ASIA FORESTAMA RAYA TERHADAP PENINGKATAN PEREKONOMIAN MASYARAKAT BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 6 TAHUN 2012 - Suhendro Suhendro; Andrew Shandy Utama; Ade Pratiwi Susanty (Ensiklopedia Social Review, 2019)
Based on Article 11 of Riau Provincial Regulation Number 6 of 2012 it is stated that the corporate social responsibility work field can be carried out in the fields of education, health, infrastructure, sports and arts, social and religious culture, environmental preservation, populist economic enterprises, empowerment of indigenous peoples, and other fields of work that significantly impact on improving the quality of society. The problem in this research is how is the implementation of corporate social responsibility of PT Asia Forestama Raya towards improving the economy of the community based on Riau Provincial Regulation Number 6 of 2012? What are the obstacles in the implementation and how are the efforts to overcome these obstacles? The method used in this research is socio-legal research. The results of this research that PT Asia Forestama Raya did not implement corporate social responsibility to empower the economy of the community in the District of Rumbai Pesisir, Pekanbaru City. The obstacles in the implementation are from the company point of view, namely the financial condition of PT Asia Forestama Raya is currently in an unstable condition so that for three years there has not been implemented a community economic empowerment program, from the community point of view, namely the lack of community knowledge regarding Riau Provincial Regulation Number 6 Year 2012, while from the government side, there is still weak supervision of the implementation of corporate social responsibility of PT Asia Forestama Raya. Efforts to overcome these obstacles are based on Article 32 of Riau Provincial Regulation Number 6 of 2012 which states that if PT Asia Forestama Raya does not implement corporate social responsibility, then the company may be subject to administrative sanctions in the form of written warnings from the Pekanbaru City Government and restrictions on business activities, suspension of business licenses, up to revocation of business licenses.